2015
DOI: 10.5194/acp-15-3289-2015
|View full text |Cite
|
Sign up to set email alerts
|

The influence of clouds on radical concentrations: observations and modelling studies of HO<sub>x</sub> during the Hill Cap Cloud Thuringia (HCCT) campaign in 2010

Abstract: Abstract. The potential for chemistry occurring in cloud droplets to impact atmospheric composition has been known for some time. However, the lack of direct observations and uncertainty in the magnitude of these reactions led to this area being overlooked in most chemistry transport models. Here we present observations from Mt Schmücke, Germany, of the HO 2 radical made alongside a suite of cloud measurements. HO 2 concentrations were depleted in-cloud by up to 90 % with the rate of heterogeneous loss of HO 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…In the case of the Anchorage based INTEX-B flights, gamma HO 2 was solely responsible for around half the uncertainty in HO 2 mixing ratios. While this sensitivity is not unexpected considering aerosol uptake of HO 2 has been shown to be important in poleward regions (Martin et al, 2003;Mao et al, 2010;Whalley et al, 2015;Christian et al, 2017), we also find considerable sensitivity to this factor in more southerly locations as well (Figs. 6,7,8,and 9).…”
Section: Aerosol Uptakementioning
confidence: 54%
See 1 more Smart Citation
“…In the case of the Anchorage based INTEX-B flights, gamma HO 2 was solely responsible for around half the uncertainty in HO 2 mixing ratios. While this sensitivity is not unexpected considering aerosol uptake of HO 2 has been shown to be important in poleward regions (Martin et al, 2003;Mao et al, 2010;Whalley et al, 2015;Christian et al, 2017), we also find considerable sensitivity to this factor in more southerly locations as well (Figs. 6,7,8,and 9).…”
Section: Aerosol Uptakementioning
confidence: 54%
“…Conversely, the box model may be better matching the measured profile just due to its lack of aerosol uptake of HO 2 . In the Arctic, the aerosol 5 uptake to HO 2 is a major loss pathway for HO 2 (Whalley et al, 2015). Without this loss pathway, the box model may have artificially high HO 2 mixing ratios.…”
mentioning
confidence: 99%
“…In the case of HO 2 and RO 2 , the radicals were first titrated with NO to OH before FAGE detection. The current mode of operation is described in detail elsewhere (Whalley et al, 2015). The HO 2 observations used as a constraint in the modelling studies reported in Sect.…”
Section: Radical Measurementsmentioning
confidence: 99%
“…Cloud droplets are also beneficial to heterogeneous and aqueous reactions (Notholt et al, 1992;Huijnen et al, 2014;Hoyle et al, 2015). Trace gases and radicals react on the surface or inside of the cloud droplets, leading to changes in the composition of secondary aerosol particles (Weller and Herrmann, 2015;Whalley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%